Analysis of Unloading Time for Fish Catches at the Kasiwa Mamuju Fish Landing Base, West Sulawesi - Ardiansyah, Muhammad; Hasrun, Khusnul Khatimah; Arwin; Danial; Umaya, Rahmi; Indriani (Journal of Fish Health, 2025)
Kasiwa Fish Landing Base (PPI) in Mamuju, West Sulawesi, is a center of fisheries activity that plays an important role in supporting the capture fisheries sector. This research aims to analyze the efficiency of unloading fish catches and the factors that influence it. The method used in this research was purposive sampling, with respondents consisting of active fishermen and port management staff. The aim of this research is to evaluate the duration of the catch unloading process at the Kasiwa Fish Landing Base (PPI) located in Mamuju, West Sulawesi. As the fishing industry advances, the importance of efficiency in unloading procedures becomes increasingly significant to boost productivity and reduce losses. This research uses an observational method with measurements of demolition time carried out over a certain period of time, as well as quantitative data analysis to identify factors that influence the duration of demolition. This includes the type of fish, volume of catch, and weather conditions at the time of unloading. The results show that the time required for disassembly ranges from 30 to 120 minutes, depending on the variables involved. It is hoped that these findings can provide suggestions for fisheries industry players to improve operational efficiency at PPI Kasiwa and become a reference for further research in the field of fisheries and marine product processing.